Electrochemical device and electronic device

By using the first silicon-carbon composite material and the second silicon-carbon composite material that adjusts the particle size and proportion, the negative electrode material layer is formed, and the problem of poor rate performance and high temperature storage performance of lithium-ion batteries is solved, and the effects of high energy density and long cycle life are achieved.

CN119650817APending Publication Date: 2025-03-18NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510100548.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have poor rate performance and high-temperature storage performance due to the volume expansion of the silicon-based negative electrode and the damage of the solid electrolyte interface (SEI) film, and are difficult to meet the needs of high energy density.

Method used

The first silicon-carbon composite material and the second silicon-carbon composite material are used to form a negative electrode material layer by adjusting the particle size and proportion, thereby improving the charge and discharge efficiency of the first circle, the cycling performance and high-temperature storage performance of the electrochemical device.

Benefits of technology

It improves the rate performance and high-temperature storage performance of lithium-ion batteries, while improving volume energy density and extending the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254125390000201
    Figure BDA0005254125390000201
  • Figure BDA0005254125390000211
    Figure BDA0005254125390000211
  • Figure BDA0005254125390000221
    Figure BDA0005254125390000221
Patent Text Reader

Abstract

The invention provides an electrochemical device and an electronic device.The electrochemical device comprises a positive pole piece, a negative pole piece and electrolyte, the negative pole piece comprises a negative pole material layer, and the negative pole material layer comprises a first silicon-carbon composite material and a second silicon-carbon composite material; the first silicon-carbon composite material comprises first silicon-carbon particles and a first carbon material layer located on the surfaces of the first silicon-carbon particles, and the second silicon-carbon composite material comprises second silicon-carbon particles and a second carbon material layer located on the surfaces of the second silicon-carbon particles. The particle size of the first silicon-carbon composite material is x [mu] m, the particle size of the second silicon-carbon composite material is y [mu] m, the number of particles satisfying 0.5 < = x < = 6 is N1, the number of particles satisfying 7 < = y < = 20 is N2, and 0.18 < = N1 / (N1 + N2) < = 0.67. The electrochemical device provided by the invention has good rate capability and high-temperature storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art

[0002] With the development of new energy technologies, electrochemical devices (such as lithium-ion batteries) are increasingly used in mobile phones, computers and other fields, and people have also put forward higher requirements for them. Commercial lithium-ion batteries based on graphite anode materials are close to their theoretical limits and are difficult to meet the current mobile information society's demand for high-energy density batteries. Silicon anode materials are considered to be the most promising and competitive emerging anode materials due to their relatively low discharge potential, high theoretical specific capacity and abundant reserves.

[0003] However, due to the volume expansion of the silicon-based negative electrode during lithiation or delithiation, the solid electrolyte interface (SEI) film is often affected by high stress and strain, which makes the SEI film easily damaged and consumes lithium ions during cycling. Therefore, it is necessary to establish an elastic and rigid SEI film on the surface of the silicon-based negative electrode. In summary, it is urgent to provide a negative electrode material with high specific capacity and conductivity to improve the rate performance and high-temperature storage performance of lithium-ion batteries, while allowing lithium-ion batteries to have a higher volume energy density. Summary of the invention

[0004] The purpose of the present application is to provide an electrochemical device and an electronic device to improve the rate performance and high-temperature storage performance of the electrochemical device.

[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0006] The first aspect of the present application provides an electrochemical device, the electrochemical device includes a positive electrode plate, a negative electrode plate and an electrolyte, the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes a first silicon-carbon composite material and a second silicon-carbon composite material, the first silicon-carbon composite material includes a first silicon-carbon particle and a first carbon material layer located on the surface of the first silicon-carbon particle, and the second silicon-carbon composite material includes a second silicon-carbon particle and a second carbon material layer located on the surface of the second silicon-carbon particle. The particle size of the first silicon-carbon composite material is xμm, the particle size of the second silicon-carbon composite material is yμm, the number of particles satisfying 0.5≤x≤6 is N1, the number of particles satisfying 7≤y≤20 is N2, 0.18≤N1 / (N1+N2)≤0.67, preferably, 0.33≤N1 / (N1+N2)≤0.5. When the particle size of the first silicon-carbon composite material and the particle size of the second silicon-carbon composite material are within the scope of this application, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material can be improved, and the cycle performance and high-temperature storage performance of the electrochemical device can be improved; at the same time, the ionic conductivity and rate performance of the first silicon-carbon composite material and the second silicon-carbon composite material can also be improved. The first silicon-carbon composite material and the second silicon-carbon composite material with a particle size within the scope of this application are mixed in proportion. When N1 / (N1+N2) is within the scope of this application, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material can be improved, and the rate performance and high-temperature storage performance of the electrochemical device can be improved. In addition, the small particles can be more fully filled between the large particles, thereby improving the volume energy density of the electrochemical device.

[0007] In one embodiment of the present application, the cross section of the negative electrode sheet includes a counting region, and the area of ​​the counting region is 19200 μm 2 , in the counting region, 20≤N1≤100, preferably, 40≤N1≤80. When N1 is within the above range, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material can be improved, the rate performance and high temperature storage performance of the electrochemical device can be improved, and the small particles can be more fully filled between the large particles, thereby improving the volume energy density of the electrochemical device.

[0008] In one embodiment of the present application, the average thickness of the first carbon material layer is 8.4nm to 13.7nm, and the average thickness of the second carbon material layer is 7.7nm to 10.5nm. The first carbon material layer and the second carbon material layer are respectively arranged on the surface of the first silicon-carbon particle and the second silicon-carbon particle, which is conducive to stabilizing the solid electrolyte interface film, and at the same time can reduce the volume expansion of silicon during the cycle process, and improve the kinetic performance, cycle performance and high temperature storage performance of the electrochemical device.

[0009] In one embodiment of the present application, the first carbon material layer comprises at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene; the second carbon material layer comprises at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene. When the first carbon material layer and the second carbon material layer respectively comprise the above materials, the conductivity of the material can be improved, which is beneficial to electron transmission, thereby improving the cycle performance and high temperature storage performance of the electrochemical device.

[0010] In one embodiment of the present application, the mass percentage of silicon in the first silicon-carbon particles is 38% to 50%; the mass percentage of silicon in the second silicon-carbon particles is 42% to 60%. When the mass percentage of silicon in the first silicon-carbon particles and the mass percentage of silicon in the second silicon-carbon particles are within the above range, the gram capacity of the first silicon-carbon composite material and the second silicon-carbon composite material can be increased, the volume energy density of the electrochemical device can be increased, and the consumption of the electrolyte during the cycle can be reduced, the cycle performance of the electrochemical device can be improved, and the kinetic performance and high-temperature storage performance of the electrochemical device can also be improved.

[0011] In one embodiment of the present application, the compaction density of the negative electrode sheet is 1.6 g / cm 3 Up to 1.8g / cm 3 When the compaction density of the negative electrode sheet is within the above range, it is beneficial to improve the dynamics of the negative electrode sheet and enhance the energy density of the electrochemical device.

[0012] In one embodiment of the present application, the electrolyte includes a first component, the first component includes at least one of 2-(fluorosulfonyl) difluoroacetyl fluoride, vinyl sulfonyl fluoride or perfluorohexane sulfonyl fluoride, and the mass percentage of the first component is 0.12% to 0.48% based on the mass of the electrolyte. When the type and mass percentage of the first component are within the above range, it is beneficial to generate an inorganic SEI interface rich in LiF, reduce the consumption of electrolyte and active lithium, and improve the cycle performance of the electrochemical device.

[0013] In one embodiment of the present application, the electrolyte includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate is 8.5% to 18.5% based on the mass of the electrolyte. When the mass percentage of fluoroethylene carbonate is within the above range, the protective effect on the negative electrode plate can be improved, the cycle gas production can be reduced, and the rate performance and high temperature storage performance of the electrochemical device can be improved.

[0014] The second aspect of the present application provides an electronic device, the electronic device comprising the electrochemical device in any of the above embodiments. The electronic device of the present application has good rate performance and high temperature storage performance.

[0015] Beneficial effects of this application:

[0016] The present application provides an electrochemical device and an electronic device, the electrochemical device includes a positive electrode sheet, a negative electrode sheet and an electrolyte, the negative electrode sheet includes a negative electrode material layer, the negative electrode material layer includes a first silicon-carbon composite material and a second silicon-carbon composite material, the first silicon-carbon composite material includes a first silicon-carbon particle and a first carbon material layer located on the surface of the first silicon-carbon particle, and the second silicon-carbon composite material includes a second silicon-carbon particle and a second carbon material layer located on the surface of the second silicon-carbon particle. The particle size of the first silicon-carbon composite material is xμm, the particle size of the second silicon-carbon composite material is yμm, the number of particles satisfying 0.5≤x≤6 is N1, the number of particles satisfying 7≤y≤20 is N2, and 0.18≤N1 / (N1+N2)≤0.67. By adjusting N1 / (N1+N2) within the scope of the present application, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material can be improved, the rate performance and high temperature storage performance of the electrochemical device can be improved, and the small particles can be more fully filled between the large particles, thereby improving the volume energy density of the electrochemical device. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0018] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0019] The first aspect of the present application provides an electrochemical device, the electrochemical device includes a positive electrode sheet, a negative electrode sheet and an electrolyte, the negative electrode sheet includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, the negative electrode active material includes a first silicon-carbon composite material and a second silicon-carbon composite material, the first silicon-carbon composite material includes a first silicon-carbon particle and a first carbon material layer located on the surface of the first silicon-carbon particle, and the second silicon-carbon composite material includes a second silicon-carbon particle and a second carbon material layer located on the surface of the second silicon-carbon particle. Among them, the first carbon material layer can be located on the entire surface or a portion of the surface of the first silicon-carbon particle, and the second carbon material layer can be located on the entire surface or a portion of the surface of the second silicon-carbon particle. In order to further improve the performance of the electrochemical device, the first carbon material layer is preferably located on the entire surface of the first silicon-carbon particle; the second carbon material layer is preferably located on the entire surface of the second silicon-carbon particle. The particle size of the first silicon-carbon composite material is xμm, the particle size of the second silicon-carbon composite material is yμm, the number of particles satisfying 0.5≤x≤6 is N1, the number of particles satisfying 7≤y≤20 is N2, 0.18≤N1 / (N1+N2)≤0.67, preferably, 0.33≤N1 / (N1+N2)≤0.5. For example, x can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, or a range consisting of any two of them; y can be 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or a range consisting of any two of them; N1 / (N1+N2) can be 0.18, 0.25, 0.3, 0.33, 0.4, 0.45, 0.5, 0.55, 0.6, 0.67, or a range consisting of any two of them.

[0020] The inventors have found that when the particle size of the first silicon-carbon composite material and the particle size of the second silicon-carbon composite material are within the scope of this application, the first silicon-carbon composite material and the second silicon-carbon composite material have a suitable specific surface area, which is conducive to adjusting the contact degree between the negative electrode active material and the electrolyte, reducing the occurrence of side reactions, improving the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material, and improving the cycle performance and high-temperature storage performance of the electrochemical device; at the same time, the ion conductivity and rate performance of the first silicon-carbon composite material and the second silicon-carbon composite material can also be improved. The first silicon-carbon composite material and the second silicon-carbon composite material with a particle size within the scope of this application are mixed in proportion. When N1 / (N1+N2) is within the scope of this application, the contact degree between the negative electrode active material and the electrolyte can be adjusted, the SEI film can be stabilized, the side reactions and lithium ion consumption during the cycle can be reduced, the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material can be improved, the rate performance and high-temperature storage performance of the electrochemical device can be improved, and the small particles can be fully filled between the large particles, thereby improving the volume energy density of the electrochemical device. In this application, "high temperature" refers to a temperature ≥80°C.

[0021] In one embodiment of the present application, the cross section of the negative electrode sheet includes a counting region, and the area of ​​the counting region is 19200 μm 2 In the counting area, 20≤N1≤100, preferably, 40≤N1≤80. The counting area can be one area or multiple areas. When the counting area is multiple areas, the sum of the areas of the multiple areas is 19200 μm 2 . N1 can be 20, 40, 60, 80, 100 or a range consisting of any two of these values. When N1 is within the above range, the contact degree between the first silicon-carbon composite material and the electrolyte can be adjusted, thereby adjusting the contact degree between the negative electrode active material and the electrolyte, stabilizing the SEI film, reducing side reactions and lithium ion consumption during the cycle, improving the first cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon composite material, improving the rate performance and high-temperature storage performance of the electrochemical device, and small particles can be more fully filled between large particles, thereby improving the volume energy density of the electrochemical device.

[0022] In one embodiment of the present application, based on the mass of the negative electrode active material, the mass percentage of the first silicon-carbon composite material is 10% to 50%, the mass percentage of the second silicon-carbon composite material is 50% to 90%, and the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material is 1:9 to 1:1, preferably 1:4 to 2:3. For example, the mass percentage of the first silicon-carbon composite material can be 10%, 20%, 30%, 40%, 50%, or a range consisting of any two values ​​therein, the mass percentage of the second silicon-carbon composite material can be 50%, 60%, 70%, 80%, 90%, or a range consisting of any two values ​​therein, and the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material can be 1:9, 1:8, 1:4, 3:7, 2:3, 1:1, or a range consisting of any two ratios therein. When the mass percentage of the first silicon-carbon composite material, the mass percentage of the second silicon-carbon composite material and the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material are within the above range, the first silicon-carbon composite material is mixed with the second silicon-carbon composite material, which can adjust the contact degree between the negative electrode active material and the electrolyte, stabilize the SEI film, reduce side reactions and lithium ion consumption during the cycle, and improve the first-cycle charge and discharge efficiency of the first silicon-carbon composite material and the second silicon-carbon composite material; and small particles can be more fully filled between large particles, thereby improving the volume energy density of the electrochemical device.

[0023] In one embodiment of the present application, the average thickness of the first carbon material layer is 8.4nm to 13.7nm, and the average thickness of the second carbon material layer is 7.7nm to 10.5nm. For example, the average thickness of the first carbon material layer can be 8.4nm, 9nm, 9.5nm, 10nm, 10.5nm, 11nm, 11.5nm, 12nm, 12.5nm, 13nm, 13.7nm, or a range consisting of any two of the values; the average thickness of the second carbon material layer can be 7.7nm, 8nm, 8.5nm, 9nm, 9.5nm, 10nm, 10.5nm, or a range consisting of any two of the values. The first carbon material layer and the second carbon material layer are respectively arranged on the surface of the first silicon-carbon particle and the second silicon-carbon particle. The average thickness of the first carbon material layer on the surface of the first silicon-carbon particle and the average thickness of the second carbon material layer on the surface of the second silicon-carbon particle are within the scope of this application, which is conducive to reducing the side reaction of the first silicon-carbon composite material and the electrolyte, stabilizing the solid electrolyte interface film, improving the conductivity of the surface of the second silicon-carbon composite material, adjusting the contact degree between the negative electrode active material and the electrolyte, reducing side reactions, and at the same time can reduce the volume expansion of silicon during the cycle, and improve the kinetic performance, cycle performance and high-temperature storage performance of the electrochemical device. The differentiated carbon layer setting is conducive to correspondingly solving the problems that may arise in the first silicon-carbon composite material and the second silicon-carbon composite material and reducing the probability of the above problems occurring in a targeted manner.

[0024] In one embodiment of the present application, based on the mass of the first silicon-carbon composite material, the mass percentage of the first carbon material layer is 0.1% to 0.5%, preferably 0.2% to 0.4%; based on the mass of the second silicon-carbon composite material, the mass percentage of the second carbon material layer is 0.04% to 0.2%, preferably 0.04% to 0.1%. For example, the mass percentage of the first carbon material layer can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, or a range consisting of any two of the values; the mass percentage of the second carbon material layer can be 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, or a range consisting of any two of the values. A first carbon material layer and a second carbon material layer are respectively arranged on the surfaces of the first silicon-carbon particle and the second silicon-carbon particle. The mass percentage of the first carbon material layer and the mass percentage of the second carbon material layer are within the scope of the present application, which is beneficial to stabilizing the solid electrolyte interface film, adjusting the contact degree between the negative electrode active material and the electrolyte, and reducing side reactions. At the same time, it can reduce the volume expansion of silicon during the cycle process, and further improve the kinetic performance, cycle performance and high-temperature storage performance of the electrochemical device.

[0025] In one embodiment of the present application, based on the mass of the first silicon-carbon composite material, the mass percentage of the first silicon-carbon particles is 99.5% to 99.9%; based on the mass of the second silicon-carbon composite material, the mass percentage of the second silicon-carbon particles is 99.8% to 99.96%. For example, the mass percentage of the first silicon-carbon particles can be 99.5%, 99.6%, 99.7%, 99.8%, 99.9% or a range consisting of any two of the values; the mass percentage of the second silicon-carbon particles can be 99.8%, 99.85%, 99.9%, 99.95%, 99.96% or a range consisting of any two of the values. When the mass percentage of the first silicon-carbon particles and the mass percentage of the second silicon-carbon particles are within the above range, the electrochemical device has a higher volumetric energy density, cycle performance and high temperature storage performance.

[0026] In one embodiment of the present application, the first carbon material layer comprises at least one of single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT) or graphene; the second carbon material layer comprises at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene; preferably, the first carbon material layer and the second carbon material layer respectively comprise different materials, for example, multi-walled carbon nanotubes are arranged on the surface of the first silicon-carbon particles, and single-walled carbon nanotubes are arranged on the surface of the second silicon-carbon particles. The first carbon material layer or the second carbon material layer can also be obtained by carbonization of other organic matter, such as tannic acid or polypyrrole. When the first carbon material layer and the second carbon material layer respectively comprise the above materials, the negative electrode active material can have better conductivity, which is beneficial to electron transmission, thereby improving the cycle performance and high temperature storage performance of the electrochemical device.

[0027] In one embodiment of the present application, based on the mass of the first silicon-carbon particles, the mass percentage of silicon in the first silicon-carbon particles is 38% to 50%; based on the mass of the second silicon-carbon particles, the mass percentage of silicon in the second silicon-carbon particles is 42% to 60%. For example, the mass percentage of silicon in the first silicon-carbon particles can be 38%, 40%, 42%, 44%, 46%, 48%, 50% or a range consisting of any two of these values; the mass percentage of silicon in the second silicon-carbon particles can be 42%, 45%, 50%, 55%, 60% or a range consisting of any two of these values. When the mass percentage of silicon in the first silicon-carbon particles and the mass percentage of silicon in the second silicon-carbon particles are within the above range, the gram capacity of the first silicon-carbon composite material and the second silicon-carbon composite material can be increased, the volume energy density of the electrochemical device can be increased, and the consumption of the electrolyte during the cycle can be reduced, the cycle performance of the electrochemical device can be improved, and the kinetic performance and high temperature storage performance of the electrochemical device can also be improved.

[0028] In one embodiment of the present application, based on the mass of the first silicon-carbon particles, the mass percentage of carbon in the first silicon-carbon particles is 50% to 62%; based on the mass of the second silicon-carbon particles, the mass percentage of carbon in the second silicon-carbon particles is 40% to 58%. For example, the mass percentage of carbon in the first silicon-carbon particles can be 50%, 52%, 54%, 56%, 58%, 60%, 62%, or a range consisting of any two of these values; the mass percentage of carbon in the second silicon-carbon particles can be 40%, 45%, 50%, 55%, 58%, or a range consisting of any two of these values.

[0029] In one embodiment of the present application, the negative electrode active material is prepared by the following preparation method: (1) providing a first silicon-carbon particle and a second silicon-carbon particle; (2) taking a first carbon material and a first silicon-carbon particle in a mass ratio of 2:998 to 7:993, adding the first carbon material to water to obtain an aqueous solution of the first carbon material, mixing the aqueous solution of the first carbon material with the first silicon-carbon particle, stirring at room temperature for 3h to 5h, and spray drying to obtain a first silicon-carbon composite material; (3) taking a second carbon material and a second silicon-carbon particle in a mass ratio of 5:9995 to 3:997, adding the second carbon material to water to obtain an aqueous solution of the second carbon material, mixing the aqueous solution of the second carbon material with the second silicon-carbon particle, stirring at room temperature for 3h to 5h, and spray drying to obtain a second silicon-carbon composite material; (4) mixing the obtained first silicon-carbon composite material and the second silicon-carbon composite material in a mass ratio of 1:9 to 1:1 to obtain a negative electrode active material. The first silicon-carbon particle and the second silicon-carbon particle in the present application can be prepared by methods known in the art, or can be purchased through commercial channels. In the present application, the solid content of the aqueous solution of the first carbon material is not particularly limited, as long as the purpose of the present application can be achieved, for example, the solid content of the aqueous solution of the first carbon material can be 2% to 4%; the solid content of the aqueous solution of the second carbon material is not particularly limited, as long as the purpose of the present application can be achieved, for example, the solid content of the aqueous solution of the second carbon material can be 2% to 4%. There is no special restriction on the instrument used for stirring, as long as the purpose of the present application can be achieved, for example, it can be a mechanical stirrer; there is no special restriction on the stirring speed, as long as the purpose of the present application can be achieved, for example, the stirring speed can be 500r / min to 800r / min; there is no special restriction on the temperature of spray drying, as long as the purpose of the present application can be achieved, for example, the temperature of spray drying can be 180℃ to 220℃.

[0030] The present application has no particular restrictions on the method for controlling the mass percentage of silicon in the first silicon-carbon particles and the second silicon-carbon particles, as long as the purpose of the present application can be achieved. For example, the mass percentage of silicon in the first silicon-carbon particles and the second silicon-carbon particles can be controlled by controlling the flow rate of the silicon-based gas passing through the porous carbon material, the deposition time of silicon on the porous carbon material, the temperature of silicon on the porous carbon material, and the like.

[0031] The present application does not particularly limit the method for regulating the particle size of the first silicon-carbon composite material and the second silicon-carbon composite material, as long as the purpose of the present application can be achieved. For example, the particle size of the first silicon-carbon particle and the second silicon-carbon particle can be regulated to correspond to the particle size of the first silicon-carbon composite material and the second silicon-carbon composite material. For example, the average particle size of the first silicon-carbon particle and the second silicon-carbon particle can be regulated by grinding the first silicon-carbon particle and the second silicon-carbon particle. For example, the particle size of the first silicon-carbon particle and the second silicon-carbon particle can be regulated by regulating the grinding time and the grinding speed. For example, when other conditions remain unchanged, the grinding time is extended, the particle size of the first silicon-carbon particle and the second silicon-carbon particle is reduced, and the particle size of the first silicon-carbon composite material and the second silicon-carbon composite material is reduced; the grinding time is shortened, the particle size of the first silicon-carbon particle and the second silicon-carbon particle is increased, and the particle size of the first silicon-carbon composite material and the second silicon-carbon composite material is increased.

[0032] The present application has no particular restrictions on the regulation method of N1 and N1 / (N1+N2), as long as the purpose of the present application can be achieved. For example, N1 and N1 / (N1+N2) can be regulated by regulating the mass ratio of the first silicon-carbon composite material and the second silicon-carbon composite material during the preparation of the negative electrode active material. When the mass ratio of the first silicon-carbon composite material and the second silicon-carbon composite material increases, N1 and N1 / (N1+N2) increase; when the mass ratio of the first silicon-carbon composite material and the second silicon-carbon composite material decreases, N1 and N1 / (N1+N2) decrease.

[0033] In the present application, the average thickness of the first carbon material layer can be regulated by regulating the mass ratio of the first silicon-carbon particles to the first carbon material. For example, when the mass ratio of the first silicon-carbon particles to the first carbon material increases, the average thickness of the first carbon material layer decreases; when the mass ratio of the first silicon-carbon particles to the first carbon material decreases, the average thickness of the first carbon material layer increases.

[0034] In the present application, the average thickness of the second carbon material layer can be regulated by regulating the mass ratio of the second silicon-carbon particles and the second carbon material. For example, when the mass ratio of the second silicon-carbon particles and the second carbon material increases, the average thickness of the second carbon material layer decreases; when the mass ratio of the second silicon-carbon particles and the second carbon material decreases, the average thickness of the second carbon material layer increases.

[0035] In one embodiment of the present application, the compaction density of the negative electrode sheet is 1.6 g / cm 3 Up to 1.8g / cm 3 For example, the compaction density of the negative electrode sheet can be 1.6 g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 Or it is a range consisting of any two values ​​therein. When the compaction density of the negative electrode plate is within the above range, it is beneficial to improve the kinetic performance of the negative electrode plate and enhance the energy density of the electrochemical device.

[0036] In the present application, the compaction density of the negative electrode sheet can be adjusted by adjusting the rolling pressure of the cold pressing process. For example, when the rolling pressure of the cold pressing process increases, the compaction density of the negative electrode sheet increases; when the rolling pressure of the cold pressing process decreases, the compaction density of the negative electrode sheet decreases.

[0037] In one embodiment of the present application, the electrolyte includes a first component, and the first component includes at least one of 2-(fluorosulfonyl) difluoroacetyl fluoride, vinyl sulfonyl fluoride or perfluorohexane sulfonyl fluoride. Based on the mass of the electrolyte, the mass percentage of the first component is 0.12% to 0.48%. For example, the mass percentage of the first component can be 0.12%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.48% or a range consisting of any two of the values. When the mass percentage of the first component is within the above range, it is beneficial to generate an inorganic SEI interface rich in LiF, reduce the consumption of electrolyte and active lithium, and improve the cycle performance of the electrochemical device.

[0038] In one embodiment of the present application, the electrolyte includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate is 8.5% to 18.5%, preferably 11.5% to 16.5%, based on the mass of the electrolyte. For example, the mass percentage of fluoroethylene carbonate can be 8.5%, 10%, 11.5%, 13%, 14%, 15%, 16.5%, 18.5% or a range consisting of any two of the values. When the mass percentage of fluoroethylene carbonate is within the above range, it can improve the protection of the negative electrode plate, reduce the cycle gas production, and thus improve the rate performance and high temperature storage performance of the electrochemical device.

[0039] In the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the negative electrode current collector, or it can be a partial area of ​​the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0040] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper, lithium-copper composite current collector, carbon-copper composite current collector, nickel-copper composite current collector or titanium-copper composite current collector, etc.

[0041] In the present application, the negative electrode active material also includes at least one of artificial graphite, natural graphite or mesophase microcarbon spheres. In some embodiments of the present application, the negative electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and conductive carbon black may include but is not limited to at least one of Super P, acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanocarbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamideimide, polyvinylidene fluoride, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon.

[0042] The present application has no particular restriction on the mass ratio of the negative electrode active material, the conductive agent, and the binder in the negative electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.

[0043] In some embodiments of the present application, the negative electrode material layer may also include a conductive agent, a binder and a thickener. The present application does not particularly limit the types of the conductive agent, binder and thickener, as long as the purpose of the present application can be achieved. For example, the conductive agent and the binder may be at least one of the aforementioned conductive agent and the aforementioned binder. The thickener may include but is not limited to at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, conductive agent, binder and thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0044] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 120 μm.

[0045] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.

[0046] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be, for example, at least one of the aforementioned conductive agent and the aforementioned binder.

[0047] In the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0048] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, a metal foil or a composite current collector can be used. For example, the metal foil may include but is not limited to aluminum foil; the composite current collector may be obtained by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate.

[0049] In the present application, the positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate, lithium titanate, lithium nickel manganese aluminum oxide, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate or at least one of spinel-type lithium nickel manganese oxide.

[0050] In the present application, the positive electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the aforementioned conductive agent and the aforementioned binder. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0051] The present application has no particular restrictions on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the single-sided positive electrode material layer is 30 μm to 150 μm.

[0052] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application does not particularly limit the conductive agent and the binder in the conductive layer, for example, it can be at least one of the aforementioned conductive agent and the aforementioned binder.

[0053] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0054] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0055] Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application has no particular restrictions on inorganic particles, for example, inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the binder, for example, the binder can be at least one of the aforementioned binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).

[0056] In the present application, the thickness of the isolation film is not particularly limited as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.

[0057] In the present application, the electrolyte includes a lithium salt and a non-aqueous solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the mass percentage of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt can be 8% to 20%.

[0058] The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, non-aqueous solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate compounds may include but are not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the mass percentage of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent can be 61.02% to 92%.

[0059] In one embodiment of the present application, the electrolyte may include a lithium salt and a non-aqueous solvent, the mass percentage of the lithium salt is as described above, and the mass percentage of the non-aqueous solvent is 80% to 92%. The electrochemical device including the above electrolyte has good high temperature storage performance and rate performance.

[0060] In one embodiment of the present application, the electrolyte may include a first component, a lithium salt and a non-aqueous solvent, the mass percentage of the first component and the lithium salt is as described above, and the mass percentage of the non-aqueous solvent is 79.52% to 91.88%. The electrochemical device including the above electrolyte has good rate performance and high temperature storage performance.

[0061] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, lithium salt and non-aqueous solvent, the mass percentage of fluoroethylene carbonate and lithium salt is as described above, and the mass percentage of non-aqueous solvent is 61.5% to 83.5%. The electrochemical device including the above electrolyte has good rate performance and high temperature storage performance.

[0062] In one embodiment of the present application, the electrolyte may include a first component, fluoroethylene carbonate, a lithium salt and a non-aqueous solvent, the mass percentages of the first component, fluoroethylene carbonate and the lithium salt are as described above, and the mass percentage of the non-aqueous solvent is 61.02% to 83.38%. The electrochemical device including the above electrolyte has good rate performance and high temperature storage performance.

[0063] In the present application, the electrochemical device also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of electrochemistry, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, and it can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and the present application does not limit the type of metal, and a metal hard shell known in the art can be used, as long as the purpose of the present application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0064] The present application does not particularly limit the type of electrochemical device, which may include any device that undergoes an electrochemical reaction. In the present application, the electrochemical device may include, but is not limited to: a lithium metal electrochemical device, a lithium ion electrochemical device (lithium ion battery), a lithium polymer electrochemical device or a lithium ion polymer electrochemical device (lithium ion polymer battery), etc.

[0065] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0066] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has good performance.

[0067] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0068] Example

[0069] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0070] Test methods and equipment:

[0071] Silicon element mass percentage test

[0072] The negative electrode sheet was plasma cut longitudinally along the thickness direction, polished by argon ion polishing technology to obtain a flat cross section, and the obtained cross section was tested using an X-ray energy spectrometer (EDS) equipped with a scanning electron microscope of model OXFORD·EDS under the conditions of an acceleration voltage of 10 kV and an emission current of 10 mA. Ten first silicon-carbon particles and second silicon-carbon particles were selected for surface scanning to test the mass percentage of silicon element, and the average value was calculated to obtain the mass percentage of silicon element in the first silicon-carbon particles and the mass percentage of silicon element in the second silicon-carbon particles.

[0073] Scanning electron microscope test

[0074] The negative electrode sheet was plasma cut longitudinally along the thickness direction and polished by argon ion polishing technology to obtain a flat cross section. The cross section of the negative electrode sheet was observed using a scanning electron microscope. The selected test instrument was: OXFORD EDS, the magnification was adjusted to 1000 times, and the total area of ​​the counting area was 19200μm 2 The first silicon-carbon composite material particles within the particle size range of 0.5 μm ≤ x ≤ 6 μm are counted, and the number of particles of the first silicon-carbon composite material is N1; and the second silicon-carbon composite material particles within the particle size range of 7 μm ≤ y ≤ 20 μm are counted, and the number of particles of the second silicon-carbon composite material is N2. N1 / (N1+N2) is obtained by calculation.

[0075] Average thickness test of the first carbon material layer and the second carbon material layer

[0076] A transmission electron microscope (model: JEM-120i) is used to observe and measure the thickness of the first carbon material layer on the surface of the first silicon-carbon particles with a particle size of 0.5μm to 6μm. The thickness of the first carbon material layer is measured at three random positions and the average value is calculated to obtain the average thickness of the first carbon material layer. Then, the thickness of the second carbon material layer on the surface of the second silicon-carbon particles with a particle size of 7μm to 20μm is observed and measured. The thickness of the second carbon material layer is measured at three random positions and the average value is calculated to obtain the average thickness of the second carbon material layer.

[0077] Compaction density test of negative electrode

[0078] After the lithium-ion battery is charged to 4.35V at 0.1C, it is discharged to 3.0V at 0.1C, and the discharge capacity is recorded as C1. Then the lithium-ion battery is charged to C1 / 2 at 0.1C, at which time the lithium-ion battery is half-charged. The lithium-ion battery is disassembled to obtain the negative electrode sheet in the half-charged state. The negative electrode sheet is cleaned with dimethyl carbonate DMC and vacuum dried, and the area is cut to S cm 2The negative electrode sheet is measured to have a thickness of H cm and a mass of Mg. The compaction density of the negative electrode sheet can be calculated to be A = M / (S×H), in g / cm 3 .

[0079] Preparation of button half-cell

[0080] (1) The first silicon-carbon composite material, acetylene black and sodium alginate are added to deionized water in a mass ratio of 80:10:10, and stirred thoroughly to form a slurry with a solid content of 40wt%. The slurry is coated on a copper foil with a thickness of 8μm by a doctor blade to form a coating with a thickness of 100μm, and after drying in a vacuum drying oven at 85°C for 12 hours, it is cut into discs with a diameter of 1cm by a punch in a dry environment to obtain a positive electrode. In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC) and dimethyl carbonate (DMC) are mixed uniformly in a mass ratio of 1:1 to obtain a mixed solution, and LiPF6 and fluoroethylene carbonate (FEC) are added to the mixed solution and stirred uniformly to obtain an electrolyte, wherein, based on the mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of FEC is 14%, and the remainder is the mixed solution. A Celgard 2400 isolation membrane with a thickness of 9μm is used. A lithium metal sheet is used as the counter electrode of the positive electrode. The positive electrode, the separator, and the lithium metal sheet are stacked in order, and the electrolyte is added to assemble the button-type half-cell Cell1 in a glove box.

[0081] (2) The second silicon-carbon composite material, acetylene black and sodium alginate were added to deionized water in a mass ratio of 80:10:10, and stirred thoroughly to form a slurry with a solid content of 40wt%. The slurry was coated on a copper foil with a thickness of 8μm with a doctor blade to form a coating with a thickness of 100μm, and dried in a vacuum drying oven at 85°C for 12 hours, and then cut into discs with a diameter of 1cm by a punch in a dry environment to obtain a positive electrode. In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed in a mass ratio of 1:1 to obtain a mixed solution, and LiPF6 and fluoroethylene carbonate (FEC) were added to the mixed solution and stirred to obtain an electrolyte, wherein, based on the mass of the electrolyte, the mass percentage of LiPF6 was 12.5%, the mass percentage of FEC was 14%, and the remainder was the mixed solution. A Celgard 2400 isolation membrane with a thickness of 9μm was used. A lithium metal sheet is used as the counter electrode of the positive electrode. The positive electrode, the separator, and the lithium metal sheet are stacked in order, and the electrolyte is added to assemble the button-type half-cell Cell2 in a glove box.

[0082] First cycle charge and discharge efficiency test

[0083] At 25°C and normal pressure, the prepared button half-cell was discharged to 0.01V at a rate of 0.05C, left to stand for 5 minutes, then discharged to 0.01V at a constant current of 50μA, and then discharged to 0.01V at a constant current of 10μA, and the discharge capacity at this time was recorded; then left to stand for 5 minutes, and then charged to 2.0V at a rate of 0.05C, and the charge capacity at this time was recorded. First cycle charge and discharge efficiency (%) = charge capacity / discharge capacity × 100%.

[0084] The first cycle charge and discharge efficiency of the tested button-type half-cell Cell1 is the first cycle charge and discharge efficiency of the first silicon-carbon composite material; the first cycle charge and discharge efficiency of the tested button-type half-cell Cell2 is the first cycle charge and discharge efficiency of the second silicon-carbon composite material.

[0085] Cyclic performance test

[0086] The test temperature is 25°C. The lithium-ion battery is charged to 4.35V at a constant current of 0.7C, and then charged to 0.025C at a constant voltage of 4.35V. After standing for 5 minutes, it is discharged to 3.0V at a constant current of 0.5C. The discharge capacity obtained in this step is the initial capacity. Carry out charging and discharging cycle tests according to the above steps, and make a ratio of the discharge capacity of each step to the initial capacity to obtain the discharge capacity retention rate of each step, and record the number of cycles of the lithium-ion battery at 25°C until the discharge capacity retention rate is 90%. The cycle performance of the lithium-ion battery is characterized by the number of cycles at 25°C until the capacity retention rate is 90%. The higher the number of cycles of the lithium-ion battery at 25°C until the capacity retention rate is 90%, the better the cycle performance of the lithium-ion battery.

[0087] Rate performance test

[0088] At 25°C, discharge the lithium-ion battery at a constant current of 0.2C to 3.0V and let it stand for 5 minutes; charge at a constant current of 0.5C to 4.35V, charge at a constant voltage of 4.35V to 0.05C, let it stand for 5 minutes, discharge at a constant current of 0.2C to 3.0V, and record the discharge capacity at this time as C0, and let it stand for 5 minutes; charge at a constant current of 0.5C to 4.35V, charge at a constant voltage of 4.35V to 0.05C, let it stand for 5 minutes, and discharge at a constant current of 2C to 3.0V, and record the discharge capacity at this time as C2.

[0089] Capacity retention rate at 2C (%) = C2 / C0×100%.

[0090] The ratio of the discharge capacity of a lithium-ion battery at 2C to 0.2C, C2 / C0, is used to characterize the rate performance of the lithium-ion battery. The larger the ratio of the discharge capacity at 2C to 0.2C, C2 / C0, the better the rate performance of the lithium-ion battery.

[0091] High temperature storage performance test

[0092] At 25°C, the lithium-ion battery is charged at a constant current of 0.5C to 4.35V, and then charged at a constant voltage of 4.35V to a current of 0.05C. At this time, the lithium-ion battery is fully charged. The thickness d0 of the lithium-ion battery is measured with a micrometer. The lithium-ion battery is then placed in an 80°C constant temperature box for high-temperature storage for 24 hours. The thickness d1 of the lithium-ion battery after storage is measured with a micrometer.

[0093] Thickness expansion ratio (%) = (d1-d0) / d0×100%.

[0094] The high temperature storage performance of lithium-ion batteries is characterized by the thickness expansion rate of lithium-ion batteries stored at 80°C for 24 hours. The smaller the thickness expansion rate of lithium-ion batteries stored at 80°C for 24 hours, the better the high temperature storage performance of lithium-ion batteries.

[0095] Example 1-1

[0096] <Preparation of negative electrode active material>

[0097] (1) Take 0.5g of MWCNT and 200g of the first silicon-carbon particles, add the MWCNT to water to prepare a MWCNT aqueous solution, stir for 0.5h, then add 200g of the first silicon-carbon particles, stir at room temperature for 4h, and spray dry to obtain a first silicon-carbon composite material. Among them, the average thickness of the first carbon material layer is 11.5nm; the solid content of the MWCNT aqueous solution is 3%; the mass percentage of silicon in the first silicon-carbon particles is 45%; the stirring instrument is a mechanical stirrer, the stirring speed is 600r / min; the spray drying temperature is 200℃.

[0098] (2) Take 0.12g of SWCNT and 200g of the second silicon-carbon particles, add SWCNT to water to prepare a SWCNT aqueous solution, stir for 0.5h, then add 200g of the second silicon-carbon particles, stir at room temperature for 4h, and spray dry to obtain a second silicon-carbon composite material. Among them, the average thickness of the second carbon material layer is 8nm; the mass percentage of silicon in the second silicon-carbon particles is 52%; the solid content of the SWCNT aqueous solution is 3%; the stirring instrument is a mechanical stirrer, the stirring speed is 600r / min; the spray drying temperature is 200℃.

[0099] (3) The artificial graphite, the first silicon-carbon composite material, and the second silicon-carbon composite material are uniformly mixed in a mass ratio of 90:3:7 to obtain a negative electrode active material.

[0100] <Preparation of negative electrode sheet>

[0101] The negative electrode active material prepared above, the binder styrene butadiene rubber (SBR), and the thickener carboxymethyl cellulose (CMC) were mixed in a mass ratio of 98:1.6:0.4, dissolved in deionized water as a negative electrode solvent, and mixed evenly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 85℃ for 4h to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After cold pressing, cutting and slitting, it is dried under vacuum conditions at 120°C for 12 hours to obtain a negative electrode sheet with a specification of 76.6mm×875mm for standby use. Among them, the compaction density of the negative electrode sheet is 1.7g / cm 3 .

[0102] <Preparation of positive electrode sheet>

[0103] The positive electrode active material, lithium nickel cobalt manganese oxide (NCM811), the conductive agent, acetylene black, and the binder, polyvinylidene fluoride (PVDF), were mixed in a mass ratio of 96.3:2.2:1.5, and the positive electrode solvent, N-methylpyrrolidone, was added and stirred evenly to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 85°C to obtain a positive electrode sheet with a single-sided coating of a positive electrode material layer, and the coating weight of the positive electrode material layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cold pressing, cutting, and slitting, it is dried under vacuum conditions at 85°C for 4 hours to obtain a positive electrode sheet with a specification of 74mm×867mm for standby use. Among them, the rolling pressure is 20T, and the compaction density of the positive electrode sheet is 4.15g / cm 3 .

[0104] <Preparation of Electrolyte>

[0105] In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC) and dimethyl carbonate (DMC) are mixed uniformly in a mass ratio of 1:1 to obtain a base solvent, and LiPF6 and fluoroethylene carbonate (FEC) are added to the base solvent and stirred uniformly to obtain an electrolyte. Wherein, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of FEC is 14%, and the mass percentage of the base solvent is 73.5%.

[0106] <Isolation film>

[0107] A polyethylene (PE) porous membrane with a thickness of 9 μm was used as the separator.

[0108] <Preparation of lithium-ion batteries>

[0109] The positive electrode sheet after welding the pole ear, the separator, and the negative electrode sheet after welding the pole ear are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain the electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, placed in an 80°C vacuum oven for 12 hours to remove moisture, and the above-prepared electrolyte is injected. After vacuum packaging, standing, formation (0.02C constant current charging to 3.5V, and then 0.1C constant current charging to 3.9V), degassing, and trimming process flow to obtain a lithium-ion battery.

[0110] Example 1-2 to Example 1-5

[0111] Except that the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material is adjusted in <Preparation of Negative Electrode Active Material> so that the values ​​of N1, N2 and N1 / (N1+N2) are as shown in Table 2, the rest is the same as Example 1-1.

[0112] Example 1-6 to Example 1-13

[0113] The same as Example 1-1 except that in <Preparation of Negative Electrode Active Material> the mass ratio of the first silicon-carbon particles to the first carbon material and the mass ratio of the second silicon-carbon particles to the second carbon material are adjusted so that the average thickness of the first carbon material layer and the average thickness of the second carbon material layer are as shown in Table 1.

[0114] Example 1-14 to Example 1-18

[0115] Except that the relevant preparation parameters in <Preparation of Negative Electrode Active Material> were adjusted according to Table 1, the rest was the same as Example 1-1.

[0116] Example 1-19 to Example 1-20

[0117] Except that the rolling pressure in the cold pressing process is adjusted in <Preparation of Negative Electrode Sheet> so that the compaction density of the negative electrode sheet is as shown in Table 2, the rest is the same as Example 1-1.

[0118] Example 2-1 to Example 2-7

[0119] Except for adding the first component in <Preparation of Electrolyte> and adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1. Among them, when the mass percentage of the first component changes, the mass percentage of the base solvent changes accordingly, and the mass ratio of each component of the base solvent and the mass percentage of the lithium salt remain unchanged.

[0120] Example 2-8 to Example 2-13

[0121] Except for adjusting the mass percentage of FEC in <Preparation of Electrolyte> according to Table 3, the rest is the same as Example 1-1. When the mass percentage of FEC changes, the mass percentage of the base solvent changes accordingly, and the mass ratio of each component of the base solvent and the mass percentage of the lithium salt remain unchanged.

[0122] Comparative Example 1

[0123] Except that the first silicon-carbon particles are directly used as the negative electrode active material in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.

[0124] Comparative Example 2

[0125] Except that the second silicon-carbon particles are directly used as the negative electrode active material in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.

[0126] Comparative Example 3

[0127] Except that the first silicon-carbon composite material is directly used as the negative electrode active material in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.

[0128] Comparative Example 4

[0129] Except that the second silicon-carbon composite material is directly used as the negative electrode active material in <Preparation of Negative Electrode Active Material>, the rest is the same as Example 1-1.

[0130] Comparative Example 5

[0131] Except that the second carbon material layer was not provided on the surface of the second silicon-carbon particles in <Preparation of Negative Electrode Active Material>, the rest was the same as Example 1-1.

[0132] Comparative Example 6

[0133] Except that the first carbon material layer was not provided on the surface of the first silicon carbon particle in <Preparation of Negative Electrode Active Material>, the rest was the same as Example 1-1.

[0134] Comparative Example 7 to Comparative Example 8

[0135] The same as Example 1-1 except that the mass ratio of the first silicon-carbon composite material to the second silicon-carbon composite material is adjusted in <Preparation of Negative Electrode Active Material> so that the values ​​of N1, N2 and N1 / (N1+N2) are as shown in Tables 1 and 2.

[0136] The preparation parameters and performance tests of various embodiments and comparative examples are shown in Table 1, Table 2 and Table 3.

[0137]

[0138]

[0139]

[0140] It can be seen from Examples 1-1 to 1-20 and Comparative Examples 1 to 8 that after the first carbon material layer and the second carbon material layer are respectively provided on the surfaces of the first silicon-carbon particles and the second silicon-carbon particles, the obtained first silicon-carbon composite material and the second silicon-carbon composite material have higher first-cycle charge and discharge efficiency, and after the first silicon-carbon composite material and the second silicon-carbon composite material are mixed in proportion, when the value of N1 / (N1+N2) is within the range of the present application, the obtained lithium-ion battery has a higher number of cycles at 25°C with a capacity retention rate of 90%, a lower thickness expansion rate when stored at 80°C for 24 hours, and a higher capacity retention rate at 2C, indicating that the cycle performance, high-temperature storage performance and rate performance of the lithium-ion battery of the present application are improved. The negative electrode active materials of Comparative Examples 1 to 6 are not within the scope of the present application, and N1 / (N1+N2) in Comparative Examples 7 to 8 is not within the scope of the present application. The number of cycles at which the capacity retention rate of the obtained lithium-ion battery is 90% at 25°C is low, the thickness expansion rate is high when stored at 80°C for 24 hours, and the capacity retention rate is low at 2C, indicating that the cycle performance, high temperature storage performance and rate performance of the lithium-ion batteries in Comparative Examples 1 to 8 are poor.

[0141] The value of N1 usually affects the high temperature storage performance and rate performance of lithium-ion batteries. It can be seen from Examples 1-1 to 1-5 that when the value of N1 is within the range of this application, the number of cycles of the lithium-ion battery obtained at 25°C with a capacity retention rate of 90% is high, the thickness expansion rate of 80°C storage for 24h is low, and the capacity retention rate at 2C is high, indicating that the high temperature storage performance and rate performance of the lithium-ion battery of this application are improved, and it also has good cycle performance.

[0142] The average thickness of the first carbon material layer and the average thickness of the second carbon material layer usually affect the cycle performance and high temperature storage performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-6 to 1-13 that when the average thickness of the first carbon material layer and the average thickness of the second carbon material layer are within the scope of this application, the number of cycles of the obtained lithium-ion battery at 25°C cycle until the capacity retention rate is 90% is high, the thickness expansion rate of 80°C storage for 24h is low, and the capacity retention rate at 2C is high, indicating that the cycle performance and high temperature storage performance of the lithium-ion battery of this application are improved, and it also has good rate performance.

[0143] The mass percentage of silicon in the first silicon-carbon particles and the mass percentage of silicon in the second silicon-carbon particles usually affect the cycle performance and high-temperature storage performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-14 to 1-17 that when the mass percentage of silicon in the first silicon-carbon particles and the mass percentage of silicon in the second silicon-carbon particles are within the scope of this application, the number of cycles of the lithium-ion battery obtained at 25°C cycle until the capacity retention rate is 90% is high, the thickness expansion rate of 80°C storage for 24h is low, and the capacity retention rate at 2C is high, indicating that the cycle performance and high-temperature storage performance of the lithium-ion battery of this application are improved, and it also has good rate performance.

[0144] The types of the first carbon material layer and the second carbon material layer usually affect the cycle performance and high temperature storage performance of the lithium ion battery. It can be seen from Examples 1-1 and 1-18 that when the types of the first carbon material layer and the second carbon material layer are within the scope of the present application, the number of cycles of the obtained lithium ion battery at 25°C cycle until the capacity retention rate is 90% is high, the thickness expansion rate of 80°C storage for 24h is low, and the capacity retention rate at 2C is high, indicating that the cycle performance and high temperature storage performance of the lithium ion battery of the present application are improved, and it also has good rate performance.

[0145] It can be seen from Examples 1-1, 1-19 and 1-20 that when the compaction density of the negative electrode plate is within the range of the present application, the obtained lithium-ion battery has a high number of cycles at 25°C with a capacity retention rate of 90%, a low thickness expansion rate after storage at 80°C for 24 hours, and a high capacity retention rate at 2C, indicating that the lithium-ion battery of the present application has good cycle performance, high temperature storage performance and rate performance.

[0146] Table 3

[0147]

[0148] Note: “ / ” in Table 3 indicates that there is no corresponding preparation parameter or substance.

[0149] The type and mass percentage of the first component usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 2-1 to 2-7 that when the type and mass percentage of the first component are within the scope of this application, the number of cycles of the obtained lithium-ion battery at 25°C until the capacity retention rate is 90% is high, the thickness expansion rate after 24h storage at 80°C is low, and the capacity retention rate at 2C is high, indicating that the cycle performance of the lithium-ion battery of this application is improved, and it also has good high-temperature storage performance and rate performance.

[0150] The mass percentage of fluoroethylene carbonate usually affects the high temperature storage performance and rate performance of lithium-ion batteries. It can be seen from Examples 1-1, 2-8 to 2-13 that when the mass percentage of fluoroethylene carbonate is within the range of this application, the number of cycles of the obtained lithium-ion battery with a capacity retention rate of 90% at 25°C is high, the thickness expansion rate of 24h storage at 80°C is low, and the capacity retention rate at 2C is high, indicating that the high temperature storage performance and rate performance of the lithium-ion battery of this application are improved, and it also has good cycle performance.

[0151] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0152] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0153] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode material layer, wherein the negative electrode material layer comprises a first silicon-carbon composite material and a second silicon-carbon composite material, wherein the first silicon-carbon composite material comprises first silicon-carbon particles and a first carbon material layer located on the surface of the first silicon-carbon particles, and wherein the second silicon-carbon composite material comprises second silicon-carbon particles and a second carbon material layer located on the surface of the second silicon-carbon particles; The particle size of the first silicon-carbon composite material is x μm, the particle size of the second silicon-carbon composite material is y μm, the number of particles satisfying 0.5≤x≤6 is N1, the number of particles satisfying 7≤y≤20 is N2, and 0.18≤N1 / (N1+N2)≤0.

67.

2. The electrochemical device according to claim 1, wherein: The cross section of the negative electrode sheet includes a counting area, and the area of ​​the counting area is 19200 μm 2 , in the counting area, 20≤N1≤100.

3. The electrochemical device according to claim 1, wherein 0.33≤N1 / (N1+N2)≤0.

5.

4. The electrochemical device according to claim 2, wherein: 40≤N1≤80。 5. The electrochemical device according to claim 1, wherein The average thickness of the first carbon material layer is 8.4 nm to 13.7 nm, and the average thickness of the second carbon material layer is 7.7 nm to 10.5 nm.

6. The electrochemical device according to claim 1, wherein The first carbon material layer comprises at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene; the second carbon material layer comprises at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or graphene.

7. The electrochemical device according to claim 1, wherein: The mass percentage of silicon in the first silicon-carbon particles is 38% to 50%; the mass percentage of silicon in the second silicon-carbon particles is 42% to 60%.

8. The electrochemical device according to any one of claims 1 to 7, wherein: The compaction density of the negative electrode plate is 1.6 g / cm 3 Up to 1.8g / cm 3 .

9. The electrochemical device according to any one of claims 1 to 7, wherein: The electrolyte includes a first component, which includes at least one of 2-(fluorosulfonyl)difluoroacetyl fluoride, vinyl sulfonyl fluoride or perfluorohexanesulfonyl fluoride. Based on the mass of the electrolyte, the mass percentage of the first component is 0.12% to 0.48%.

10. The electrochemical device according to any one of claims 1 to 7, wherein: The electrolyte includes fluoroethylene carbonate, and based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 8.5% to 18.5%.

11. An electronic device comprising the electrochemical device according to any one of claims 1 to 10.